Produção e caracterização de filmes isolados contendo biopolímero arabinogalactana extraído das folhas de Pereskia aculeata Miller (Ora-Pro-Nóbis) - Coppini, Gustavo (2021)
Solid oral dosage forms represent the most used category among all the dosage forms, especially to tablets, which can be classified into conventional release tablets and modified release tablets. The latter have several advantages, such as a better adhesion of the patient, better release/absorption of the API and reduction of plasma fluctuation of the drug. Objectives: The objective of this work is the production of films, including the biopolymer arabinogalactan extracted from the leaves of Pereskia aculeata Miller together with ethylcellulose, in order to verify the film-forming capacity of this biopolymer, to use it in modified release formulations. Methodology: The biopolymer was extracted from the leaves of Pereskia aculeata Miller through aqueous extraction with an ethanolic form. The films were obtained by the solvent evaporation method and taken as to macroscopic and morphological characteristics, transparency, loss of mass on desiccation, infrared spectroscopy (FTIR), thermogravimetry (TGA), differential image calorimetry (DSC), diffraction X-ray (DRX), scanning electron microscopy (SEM), water vapor transmission (TVA) and swelling index (Ii%). Results: Through FT-IR, DRX and thermal analysis, it was possible to show that there was no incompatibility between the compounds of the formulations, in addition to an improvement in the thermal profile of the membranes. Through the X-ray diffraction, an amorphous characteristic of the membranes constituted with the natural polysaccharide was found and the beginning of a possible crystalline organization in the membranes containing the reticular polysaccharide. In evaluating the loss of mass, TVA and Ii%, a change in the profiles of TVA and Ii% was observed with the increase in the concentration of arabinogalactan. Conclusions: Results showed that the addition of arabinogalactan resulted in a good performance of the films in TVA and Ii% tests, added to this, the polysaccharide crosslinking proved effective in reducing the hydro solubility of the polysaccharide in addition to have improved the physical characteristics of the membranes. Thus, the addition of arabinogalactan with ethyl cellulose proved to be a promising association in the modulation of drug release. Through this association, it was possible to circumvent the insolubility characteristics of ethyl cellulose, as well as the characteristic of high solubility of the arabinogalactan, thus allowing the dosage form to pass intact through the stomach and the drug can be released into the intestine, by the addition of the polysaccharide.